ARTISTIC THINKING AND STREAM OF CONSCIOUSNESS IN THE SHORT STORIES OF WILLIAM FAULKNER AND NAZAR ESHONQUL: A COMPARATIVE STUDY - Safarova Fotima Ne’matulla qizi (International Journal of Literature and Language Studies, 2026)
This article investigates the convergence of artistic thinking and stream-of-consciousness technique in the short fiction of William Faulkner, one of the foremost American modernists, and Nazar Eshonqul, a prominent contemporary Uzbek prose writer. Drawing on the theoretical frameworks of modernist poetics and cognitive narratology, the study conducts a close comparative analysis of selected short stories to examine how both authors deploy interior monologue, temporal fragmentation, non-linear narrative, sensory layering, and psychological depth to construct subjective realities. While Faulkner channels the traumatic memory of the American South through Freudian-inflected consciousness, Eshonqul employs philosophical introspection rooted in Eastern thought, mysticism, and the existential tensions of post-Soviet Uzbek identity. Despite the geographical and cultural distance between these two literary traditions, the article identifies remarkable structural and aesthetic parallels in their treatment of consciousness as a narrative medium. The findings contribute to ongoing cross-cultural dialogue between Western modernism and contemporary Uzbek literature, demonstrating that the stream-of-consciousness technique transcends its Euro-American origins to function as a universal vehicle for artistic thinking.